Sustainable Tourism Development in Nusa Penida: Inclusive, Digital, and Sustainable Strategies - Putu Surya Laksana Rahjasa; Made Darmiati; Made Artajaya; I Gede Ngurah Primanda S Rahadiarta; Ni Putu Evi Wijayanti; Putu Ayu Aryasih (Green Publisher Indonesia, 2025)
This study analyses the potential, challenges, and strategies for sustainable tourism development in Nusa Penida through a SWOT approach supported by field observations and semi-structured interviews. This study uses a descriptive qualitative method with data collected from field practice activities of students of the Travel and Tourism Business Study Program, Bali Tourism Polytechnic, in June 2025. The SWOT analysis was formulated into an IFAS and EFAS matrix, and validated by triangulation using literature and reports from relevant agencies. The results show that Nusa Penida has key strengths in the form of iconic natural beauty and strong local cultural potential, but faces serious challenges such as limited infrastructure, minimal public facilities, limited human resource capacity, and pressure on the environment. The IFAS and EFAS results place Nusa Penida in the aggressive quadrant, indicating the need to leverage internal strengths to capture significant external opportunities. Recommended development strategies include strengthening infrastructure and safety, digitizing tourism services, developing inclusive tourism packages, increasing local human resource capacity, and community-based environmental conservation. With a collaborative and sustainable approach, Nusa Penida has the potential to become a leading tourist destination that is resilient, inclusive, and adaptive to the dynamics of global tourism.